The race relations competence workshop: theory and results - Alderfer, Clayton P; Alderfer, Charleen; Bell, Ella Louise; Jones, Jimmy (Human Relations, 1992)
This paper presents the theoretical basis and the associated perceptions of race relations that characterized a race relations competence workshop which served as the educational component of an overall program to improve race relations among managers within the fictitiously named XYZ Corporation. Workshop activities combined didactic and experiential methods and focused on group and individual levels of learning based on embedded intergroup relations theory. An assessment of the race relations competence workshop was carried out as part of an overall effort to evaluate the race relations improvement program in the company. Employing measures of both global evaluation and perceptions of race relations among managers, the study showed that Blacks evaluated the workshop more favorably than Whites, that reports of having information about the workshop were positively associated with favorable evaluations of the workshop, that workshop participants more than nonparticipants were likely to perceive Whites as hurting Blacks and less likely to perceive Blacks as hurting Whites. Additional analyses showed that, while the workshop generally had favorable effects for participants, the groups most likely to show unfavorable consequences were White male first level managers younger than 41 years and White female first level managers older than 40 years.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/126-048-778-075-671 tex.type: [object Object]
Keywords: dept.mft; race relations competence workshop

Diagnosing race relations in management - Alderfer, Clayton P; Alderfer, Charleen; Tucker, L M; Tucker, Robert C (The Journal of Applied Behavioral Science, 1980)
This paper reports the theory, process, results, and consequences of diagnosing the race relations among managers of a large industrial corporation. A four person diagnostic team consisting of a black female, black male, white female, and white male, aided by a 12-person advisory committee of similar race/sex composition, developed an organic questionnaire and administered it to more than 600 managers. Data were collected and analyzed on general race relations, management groups, hiring, advancement, firing, actions for change, and reactions to the study. Analysis showed that the state of race relations in the company was related to a variety of systemic conditions including the ideas and feelings of individuals, the perceptions and actions of key groups, and the structure of the whole organization. As a result of the diagnosis, management committed itself to an action plan that addressed all the problematic issues uncovered by the diagnosis. © 1980, Sage Publications. All rights reserved.
82 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-316-845-829-383 tex.type: [object Object]
Keywords: dept.mft